Microscopic and Spectroscopic Investigation of (AlxGa1–X)2O3 Films: Unraveling the Impact of Growth Orientation and Aluminum Content - Jith Sarker; Prachi Garg; Abrar Rauf; Ahsiur Rahman Nirjhar; Hsien‐Lien Huang; Menglin Zhu; A. F. M. Anhar Uddin Bhuiyan; Lingyu Meng; Hongping Zhao; Jinwoo Hwang; Eric Osei‐Agyemang; Saquib Ahmed; et al. (Advanced Materials Interfaces)
Abstract (AlxGa1–x)2O3 is an ultrawide‐bandgap semiconductor with a high critical electric field for next‐generation high‐power transistors and deep‐ultraviolet photodetectors. While (010)‐(AlxGa1–x)2O3 films have been studied, the recent availability of (100), (2¯01)‐Ga2O3 substrates have developed interest in (100), (2¯01)‐(AlxGa1–x)2O3 films. In this work, an investigation of microscopic and spectroscopic characteristics of (100), (2¯01), (010)–(AlxGa1–x)2O3 films is conducted. A combination of scanning transmission electron microscopy, atom probe tomography (APT), and first‐principle calculations (DFT) is performed. The findings reveal consistent in‐plane chemical homogeneity in lower aluminum content (x = 0.2) films. However, higher aluminum content (x = 0.5), showed inhomogeneity in (100), (010)–(AlxGa1–x)2O3 films attributed to their spectroscopic properties. The study expanded APT's capabilities to determine Ga─O and Al─O bond lengths by mapping their ion‐pair separations in detector space. The change in ion‐pair separations is consistent with varying orientations, irrespective of aluminum content. DFT also demonstrated a similar trend, concluding that Ga─O and Al─O bonding energy has an inverse relationship with their bond length as crystallographic orientations vary. This systematic study of growth orientation dependence of (AlxGa1–x)2O3 films’ microscopic and spectroscopic properties will guide the development of new (100) and (2¯01)‐(AlxGa1–x)2O3 along with existing (010)–(AlxGa1–x)2O3 films.